2023
DOI: 10.1111/wvn.12646
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being in acute care nurse managers: A risk analysis of physical and mental health factors

Abstract: Background Nurse managers have experienced tremendous stress during the COVID‐19 pandemic, contributing to negative psychological outcomes. Positive professional well‐being is a construct that can be promoted to mitigate poor psychological outcomes and burnout in nurses. Little is known about the health, healthy behaviors, effects of stress on homelife, and well‐being of nurse managers in the United States (U.S.). Aims The aims of the study were to explore nurse managers’ well‐being related to self‐reported st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The findings revealed high levels of stress, with many nursing managers experiencing work-related stress spilling over into their personal lives, thus contributing to burnout and emotional problems. The study highlighted the need for interventions to improve the well-being of nursing managers, including administrative support and policy changes [67] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The findings revealed high levels of stress, with many nursing managers experiencing work-related stress spilling over into their personal lives, thus contributing to burnout and emotional problems. The study highlighted the need for interventions to improve the well-being of nursing managers, including administrative support and policy changes [67] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The working ward with the highest stress load in this study was the emergency department. The nature and working environment of different departments can affect the pressure and organizational support of nursing staff [ 37 ]. From the perspective of sudden public health emergencies, emergency medical staff on the front line of hospitals face higher occupational exposure risks, work overload, and serious psychological impact.…”
Section: Discussionmentioning
confidence: 99%
“…answers to two open-ended survey questions collected as a part of a larger research study with acute care NMs (Martin et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In the larger study, participants completed a web-based survey consisting of questions regarding their demographic and work characteristics, the Well-being Index for Nurses, and questions about their personal health perceptions and habits. Quantitative study results from these questions were analyzed separately and reported in (Martin et al, 2023). Participants also were asked to complete two open-ended short-answer questions in the survey with no character limit imposed.…”
Section: Participantsmentioning
confidence: 99%